1964
DOI: 10.1002/ijch.196400040
|View full text |Cite
|
Sign up to set email alerts
|

The Autoxidation of I in Ice

Abstract: The rate of the autoxidation of 1-is largely enhanced in ice u compared to the liquid state. A peculiar effect of acidity on the rate hu been observed. Remarkable inhibition is caused by doping the ice with some foreign substances. The rate in H 20-ice is 2-3 times larger than in~v-ice. The frozen system displays a high photochemical sensitivity.The remarkable chemical and radiative properties of frozen solutions, which were first pointed out by Szent-Gyorgyi [1 J, have been the subject of several works. In pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1969
1969
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
(4 reference statements)
1
11
0
Order By: Relevance
“…The reaction between iodide ions and nitrous acid, under both freezing conditions and in nonfrozen solutions, produces greater quantities of product when dissolved oxygen is present. , Such behavior is similar to that observed in many other freeze-induced reactions. In fact, both iodide and nitrite ions undergo greatly enhanced oxidation by dissolved oxygen when they are frozen separately in dilute solutions. ,, In order to determine the role of dissolved oxygen for the current reactions under study, two further experiments were carried out. In the first, mixture 1 ([Br − ]/[I − ] = 10) was frozen under very acidic conditions (pH 2.7) in the absence of dissolved oxygen.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reaction between iodide ions and nitrous acid, under both freezing conditions and in nonfrozen solutions, produces greater quantities of product when dissolved oxygen is present. , Such behavior is similar to that observed in many other freeze-induced reactions. In fact, both iodide and nitrite ions undergo greatly enhanced oxidation by dissolved oxygen when they are frozen separately in dilute solutions. ,, In order to determine the role of dissolved oxygen for the current reactions under study, two further experiments were carried out. In the first, mixture 1 ([Br − ]/[I − ] = 10) was frozen under very acidic conditions (pH 2.7) in the absence of dissolved oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…As observed in the case where X = Cl − , it was shown that the freezing process itself can lead to unexpected chemical behavior . Previous reports in the literature have shown that a variety of reactions are in fact accelerated as a result of the freezing process. In particular, a number of atmospherically relevant autoxidation reactions, such as those involving nitrite, iodide, sulfide, or sulfite ions, are known to be promoted when dilute solutions are frozen. , Indeed, an acceleration of reaction rates up to 10 5 times above those at room temperature have been reported in the literature . When a solution of dilute electrolytes is frozen, it is known that some species are incorporated more readily into the ice than others, the so-called Workman−Reynolds effect. , The concentrations of electrolytes in the liquid phase may increase dramatically as liquid water is removed to the growing solid phase and, as the freezing front advances, the remaining liquid becomes trapped between grain boundaries, leading to the formation of unfrozen, liquid-phase “micropockets”.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…For example, it has been shown that both sulfur dioxide and sulfide ions incorporated into ice are oxidized to sulfate ions (Valdez et al, 1989;Finnegan et al, 1991, Betterton and. Similarly iodide and bromide ions become oxidized to higher valence species when frozen (Eyal et al, 1964). It was later discovered that the N(III) species, NO − 2 and HONO, can be oxidized by molecular oxygen to nitrate ions upon freezing in aqueous solution at a rate about 10 5 faster than that found at room temperature (Takenaka et al, 1992).…”
Section: Impacts Of Freezing On Snowpack Impurities and Reactionsmentioning
confidence: 99%